THE NATIONAL-VICTIMISM: BETWEEN THE RIGHT OF RESISTANCE AND THE RIGHT OF SELF-DETERMINATION. A NEW TYPE OF RACISM? - Gago Guerrero, Pedro Francisco (2019)
National-victimism is based on an ideology of prophylactic racism that will have to create a political strategy in order not only to make independent a territory of the nation of which it forms part, expropriating it without just cause, but also to form a despotic state of racially superior beings. Being an adaptation of racism to the new realities, they use the defense of subjective rights and the right of peoples to dominate and transform citizens who have not evolved or have had a genetic tare. That is why national-victimism will be one more current that rejects human dignity and equality. Its strategy to achieve its objectives will consist of using the right of self-determination, guaranteed by the right of resistance, to once achieved the goals pursued, impose a right of subordination, eliminating legal equality and creating a new Lebensraum.